The use of perennial needles as biomonitors for recently accumulated heavy metals - Turkyilmaz, Aydin; Sevik, Hakan; Cetin, Mehmet (Springer Science and Business Media LLC, 2018)
The measurement of heavy metal concentrations in plants is important both for determining their ability to remove these pollutants from the air to increase its quality, and for the monitoring of air quality. Previous studies have mostly focused on the use of annual leaves of broadleaved species as biomonitors. In this study, the aim was to determine the heavy metal accumulation of the perennial needles of some conifers. In almost all the species studied, concentrations of heavy metals were found to increase with the age of the tree, but this increase was not linear. There were significant differences between the species in terms of heavy metal accumulation. The highest concentrations were for Fe in Pinus nigra, Zn in Picea pungens, Pb in Pinus sylvestris, and for all the other heavy metals in Abies bornmulleriana. This study indicates that A. bornmulleriana is particularly useful as a biomonitor for many heavy metals, and also has the potential to remove heavy metals from the air.
Keywords: 13. Climate action; 15. Life on land